Tactical satellite orbital simulation and requirements study - Bedrosian, Edward; Cesar, Edison, 1924-; Clark, John R.; Huth, Gaylord, 1940-; Poehlmann, Katherine M., 1942-; Propper, Phil.; Rand Corporation; Arroyo Center. Force Development and Technology Program; United States. Army. (Santa Monica, CA : RAND, 1993)
This Note documents the results of a preliminary analysis of space communications requirements employing scenarios for military operations in three widely separated geographical areas where U.S. contingency operations could occur. The first scenario is set in Southwest Asia and is similar to Desert Shield/Storm, except with jamming; the second is set in Korea to typify a large operation between in-place forces, again with jamming; and the third is set in Argentina to typify a small operation in a remote location. Based on Desert Shield/Storm experience and on RAND's experience with military communications satellite systems, the study argues that jamming will present a serious threat and that jam-resistant communication satellites and portable tactical jam-resistant earth terminals must continue to be fielded and developed. To test the operational scenarios under realistic circumstances, a comprehensive computer simulation will need to be developed -- one that involves developing a system configuration tool capable of configuring a satellite communication system using the specified equipment and communications requirements within the spatial and temporal relationships laid out in the scenarios.
Prepared within "the Force Development and Technology Program of the Arroyo Center"--Preface.
Includes bibliographical references (p. 59).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: United States. -- Army -- Communication systems -- Computer simulation; Artificial satellites in telecommunication -- Computer simulation; Iraq-Kuwait Crisis, 1990-1991.